Kajian Kalimat Efektif pada Laporan Berita Reporter Metro TV - Devita, Marieta Bona; Putrayasa, I G.N.K.; Madia, I Made (Humanis; Vol 24 No 1 (2020)DO - 10.24843/JH.2020.v24.i01.p08, 2020)
This research entitled “The News Report of Metro TV Reporter: The research of effective sentence”. The aim of this research was to find out the description, error, and percentage of effective and ineffective sentence in the news report of Metro TV reporter. The used theory refer to some ideas from the experts, those are Keraf (1980), Razak (1986), Sugono (2001), Putrayasa (2014), and Agency of Language Development and Coaching (2014). The used method to collect the data in this research was observation method, then the data was analyzed with qualitative descriptive method, quantitative method, and agih method. Method of presenting analyzed data that used in this research were formal and informal method. Data source in this research was from twelve videos of news report of Metro TV reporter in 2018. The result of this research showed that Metro TV reporter's understanding of the use of effective sentences reach 30, 22% from 12 news reports. This is proven by the discovery of 97 ineffective sentences out of 139 sentences. The error of ineffective sentence in news report of Metro TV reporter was divided into four kinds, those were the accuracy of information 7 sentences (5.03%), stiffness 6 sentences (4,32%), efficiency 48 sentences (34.53%), multiple errors and plural 36 sentences (25.90%). The total percentage of the error ineffective sentence as a whole was 69.78%. Based on this percentage, the highest frequency of errors was in the aspect of efficiency.